2013
DOI: 10.1371/journal.pone.0060042
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Metabiome by Rifaximin in Patients with Cirrhosis and Minimal Hepatic Encephalopathy

Abstract: Hepatic encephalopathy (HE) represents a dysfunctional gut-liver-brain axis in cirrhosis which can negatively impact outcomes. This altered gut-brain relationship has been treated using gut-selective antibiotics such as rifaximin, that improve cognitive function in HE, especially its subclinical form, minimal HE (MHE). However, the precise mechanism of the action of rifaximin in MHE is unclear. We hypothesized that modulation of gut microbiota and their end-products by rifaximin would affect the gut-brain axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
340
6
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(379 citation statements)
references
References 45 publications
(53 reference statements)
13
340
6
3
Order By: Relevance
“…[21][22][23][24] A systematic study of MHE therapy with rifaximin was performed by our group in which we found a significant improvement in cognitive performance. 25 This was accompanied by an enhanced working memory performance via facilitation of the functioning of subcortical structures, greater inhibitory control by modulation of fronto-parietal activation, and improved white matter integrity in MHE after rifaximin on multi-modal brain MR imaging. We also found improved neural network connectivity between frontal and parietal structures and, in particular, facilitation of the left parietal operculum.…”
Section: Mhe Therapymentioning
confidence: 91%
“…[21][22][23][24] A systematic study of MHE therapy with rifaximin was performed by our group in which we found a significant improvement in cognitive performance. 25 This was accompanied by an enhanced working memory performance via facilitation of the functioning of subcortical structures, greater inhibitory control by modulation of fronto-parietal activation, and improved white matter integrity in MHE after rifaximin on multi-modal brain MR imaging. We also found improved neural network connectivity between frontal and parietal structures and, in particular, facilitation of the left parietal operculum.…”
Section: Mhe Therapymentioning
confidence: 91%
“…These studies suggest that cognitive impairment in HE patients may be caused by gut microbiota disruption, because rifaximin and lactulose directly or indirectly act on gut microbiota, inhibiting the growth of ammonia-producing bacteria and reducing ammonia production in the gut. They improve the cognitive impairment of HE patients by changing the gut microbiota and metabolites (Bajaj et al, 2013). …”
Section: Some Common Diseases and Admentioning
confidence: 99%
“…Its use does not seem to significantly alter the stool microbiome or increase antibiotic resistance, and its use has been associated with lower incidence of development of SBP. [52][53][54] 9. Answers: B, C and E Cholangiocarcinoma (CCA) is the second most common type of primary liver cancer, and forms $3% of all gastrointestinal neoplasias.…”
Section: Answers: B and Cmentioning
confidence: 99%